Antioxidant and antidiabetic activity of the endophytic fungus Alternaria alternata isolated from Rosmarinus officinalis L. - Rabab Majead Abed; Batoul Mohammed Alwan (Plant Science Today, 2024)
The results of the isolation of internal fungi showed that 70% of the leaves of the rosemary plant that were examined contained one isolation of the endophytic fungi by one fungal colony for each plant piece of rosemary plant leaves. The results of the phenotypic and microscopic examination of the internal fungus isolates showed that they belong to the same species: the fungus Alternaria alternata. The diagnosis was confirmed by PCR technique, and the isolates were compared with the global isolates registered in the gene bank (GenBank MF099865.1 and OQ764793.1), with which they matched 100%. The results of the evaluation of the biological efficacy of the extract of the internal fungi A. alternata showed that it possesses vital properties of an antioxidant by inhibiting the activity of free radicals 2,2-diphenyl-1-picrylhydrazyl (DPPH) The extract internal fungi recorded a high percentage of inhibitory activity of free radicals and was 93.5% at a concentration of 500 mg, we note that the inhibitory effect increased with increasing concentration of the extract. The results of the current study also showed that the extract of the internal fungi A. alternata. It showed efficiency in inhibiting the activity of the alpha-amylase enzyme, and therefore, it works as an antidiabetic, as it achieved an inhibition rate of alpha-amylase activity of 75.55%.